Learning to learn: research into adaptive and collaborative management of community forests - McDougall, C. (2001)
The author highlights conceptual, substantive and methodological aspects of participatory action research (PAR) into adaptive collaborative management (ACM) of community forest in some selected FUGs in the Hills of Nepal. Three main concepts of ACM identified as the core of research include: collaboration among stakeholders, conscious social learning and application of learning feedback to management. Ten specific elements have been recently innovated around the three broad areas of ACM, and the research team uses them as a basis to assess and facilitate action research at local level. The author indicates that all the four partner FUGs have shown significantly greater progress towards improving collaboration, conscious social learning and application of feedback than during the time before the PAR. Future activities of research are expected to enable FUGs to achieve goals, and at the same time enable researchers to draw broad lessons as regards conditions, processes and outcomes of ACM, along with potential strategies and tools to facilitate the process.